2014
DOI: 10.1039/c4sc00298a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale self-assembled multivalent (SAMul) heparin binders in highly competitive, biologically relevant, aqueous media

Abstract: This paper investigates small molecules that self-assemble to display multivalent ligand arrays for heparin binding. In water, the self-assembled multivalent (SAMul) heparin binder is highly competitive with the current clinical heparin reversal agent, protamine. On addition of salt, the dimensions of the self-assembled nanostructure increase. This unique feature is due to the dynamic, responsive nature of assembly, predicted using multiscale modelling and proven experimentally, enhancing heparin binding of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Given the clinical interest of heparin binding systems, we also probed the ability of these compounds to bind heparin in more competitive conditions, performing the MalB assay in human serum (Table ). As expected from our previous work on SAMul nanostructures, serum had an adverse effect on binding, and the CE 50 values increased. As in buffer, C18‐1 remained the most effective heparin binder, however, differences between all three systems somewhat decreased.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Given the clinical interest of heparin binding systems, we also probed the ability of these compounds to bind heparin in more competitive conditions, performing the MalB assay in human serum (Table ). As expected from our previous work on SAMul nanostructures, serum had an adverse effect on binding, and the CE 50 values increased. As in buffer, C18‐1 remained the most effective heparin binder, however, differences between all three systems somewhat decreased.…”
Section: Resultssupporting
confidence: 88%
“…The ligands are located at the nanoscale binding interface and play the key role in mediating the interactions between the SAMul cation and the polyanion—there is a clear molecular‐scale mechanism for this effect. Multiscale modelling methods in which atomistic and mesoscale methods are combined, provide a uniquely powerful toolkit, and have allowed us to gain fundamental insight into such molecular recognition processes at nanoscale binding interfaces ,…”
Section: Introductionmentioning
confidence: 99%
“…8). 54 Furthermore, comparison of the heparin binding of C 22 -G1 with an analogue with no hydrophobic unit demonstrated that the Fig. 8 Structure of C 22 -G1, multiscale modelling simulation of C 22 -G1 self-assembled into a multivalent structure and bound to heparin, and binding study comparing the ability of C 22 -G1, current therapy protamine, and a non-self-assembling precursor (P-G1) indicating that in buffer, the self-assembling nanosystem outperforms protamine, and that there is a clear quantifiable SAMul binding effect.…”
Section: How Major Surgery Inspired Samul Heparin Binders and Sensorsmentioning
confidence: 99%
“…In the panorama described above, during the last 5 years our laboratory, in collaboration with different international groups, has designed and produced a series of amphiphilic molecules bearing dendritic portions as polar heads and various hydrocarbon chains as hydrophobic moieties, able to self-organize into supramolecular nanostructures of different size and shape with the unique capability of selectively binding the two major polyanions, heparin and DNA [21,22,23,24,25,26,27,28,29]. This, with the goal of employing the resulting self-assembled dendrimers as protamine replacer and gene delivery nanovectors, respectively.…”
Section: Introductionmentioning
confidence: 99%